Aristotle’s considerations on the nature of numbers (“Metaphysics”, XIII, 6–7) - Nowakowski, Dawid (Hybris, 2014)
The article analyses the part of Aristotle’s Metaphysics, which deals with the Plato’s idealistic theory of numbers. In the first six sections it describes and defines a few basic concepts of mathematics, in the seventh section it clarifies Aristotle’s opinion on the possible philosophical attitudes toward the nature of numbers. The next sections are devoted to logical analysis of Aristotle’s reasoning in refuting the Plato’s theory of numbers. The article ends with a short conclusion, where is indicated a possible connection between proposals of Aristotle and foundations of Kantian philosophy.